Antifungal activity of palmatine against strains of Candida spp. resistant to azoles in planktonic cells and biofilm - Campos, Rosana de Sousa (2019)
The incidence of fungal infections has increased and it is necessary to seek new antifungals that also act against resistant strains. Palmatine is a protoberberine alkaloid noteworthy for its various pharmacological properties, including antifungal properties. The objective of this study was to evaluate the activity of palmatine against Candida spp. strains resistant to azole in planktonic cells and biofilm, and to elucidate the possible mechanism of cell death. Palmatine showed an antifungal activity with MICs ranging from 32 to 128 μg/mL. In the formed biofilms, palmatine reduced by 50% cell viability at the concentration of 20x MIC (C. albicans) and 10x MIC (C. tropicalis and C. parapsilosis). In the formed biofilms, the same percentage of inhibition was achieved at a concentration of 1x MIC (C. albicans) and 2x MIC (C. tropicalis and C. parapsilosis). It was found that palmatine causes damage to DNA, promotes mitochondrial depolarization and increasing the externalization of phosphatidylserine, suggesting cell death by apoptosis. The antifungal action of palmatine in Candida spp. resistant to azoles in planktonic cells and biofilm formed and in formation, as well as the fact of not having presented cytotoxicity in mammalian cells, point to a promising new anti-candida molecule.